Correlation of Pain, Physical Function and Radiography With Osteoarthritis of The knee - Ahmed, Syed Mozaffar; Emran, Mohammed; Hasan, Md Israt; Newaz, Fatema; Ahmed, Badrunnesa; Khandaker, Md Nuruzzaman; Emran, Md Ali (KYAMC Journal, 2020)
Background: Osteoarthritis (OA) of the knee is a major public health issue. It is important to have a clear understanding about the relationship between clinical features (Pain, functional impairment) and radiographic findings to select appropriate treatment option. Objectives: To investigate the relationship between pain, loss of physical function, and radiographic findings in OA of the knee joint. Materials and Methods: A cross sectional study on 90 patients aged 40 years and above with OA of the knee joint selected randomly. Severity of the knee pain and functional impairment were measured using the Bangla version of WOMAC (Western Ontario and McMaster Universities Osteoarthritis index). Radiograph of the knee joint were assessed with the Kellgren- Lawrence grading scale. Results: The mean of the age, BMI (body mass index) and duration of pain was respectively 54.2 (± 9.5) years, 26.0 (± 3.4) kg/m2 and 3.6 (± 2.8) years. Male female ratio was 1:1.6. 55% of the patients had the Visual Analogue Scale (VAS) score of 1-3. The Pain and physical function were associated with OA of the knee where the mean physical function score was 45.1 ± 4.2 in patients who had pain score of >10. However pain and physical function was not associated with the radiographic findings of the OA of the knee. Conclusion: The treatment planning for the OA of the knee should be based on clinical presentation rather than radiographic findings. KYAMC Journal Vol. 10, No.-4, January 2020, Page 173-178